The effect of prenatal lithium exposure on the neuropsychological development of the child. (5th October 2021) - Poels, Eline M. P.; Schrijver, Lisanne; White, Tonya J. H.; Roza, Sabine J.; Zarchev, Milan G.; Bijma, Hilmar; Honig, Adriaan; van Kamp, Inge L.; Hoogendijk, Witte J. G.; Kamperman, Astrid M.; Bergink, Veerle
Abstract: Objectives: Lithium is an effective treatment for bipolar disorder, also during pregnancy to prevent the recurrence of episodes in the perinatal period. Little is known about the neuropsychological development of lithium‐exposed offspring. The current study was designed to investigate neuropsychological functioning in lithium‐exposed children with the aim to provide further knowledge on the long‐term effects of lithium use during pregnancy. Methods: Participants were offspring of women with a diagnosis of bipolar spectrum disorder, aged 6–14 years. In total, 99 children participated in the study, 56 were exposed to lithium in utero and 43 were not exposed to lithium. Neuropsychological tests were administered, including the Snijders‐Oomen Nonverbal Intelligence Test and the NEPSY‐II‐NL assessment. Linear and negative binomial regression models were used to investigate the association between prenatal lithium exposure and neuropsychological functioning. In secondary analyses, the association between lithium blood level during pregnancy and neuropsychological functioning was assessed. Additionally, norm scores and percentiles for task outcomes were calculated. Results: Lithium use during pregnancy was associated with the total number of mistakes made on the Auditory Attention task, but not statistically significant after full adjustment for potential confounding factors. No association between prenatal lithium exposure and IQ was found. Also, no relationship between lithium blood level during pregnancy and neuropsychological functioning was found after adjustment for potential confounders. Task outcomes in both groups were comparable to the general population. Conclusion: In this study, we found no evidence for significantly altered neuropsychological functioning of lithium‐exposed children at the age of 6–14 years, when compared to non‐lithium‐exposed controls.